DBU‐Mediated Reaction of 3‐Chlorooxindole and 9‐Xanthyl Fluorene for Synthesis of 3‐Arylidene Oxindole - Nitchakan Purahong; Thapong Teerawatananond; Nawasit Chotsaeng; Pattarapapa Janthakit; Phattananawee Nalaoh; Vinich Promarak; Chutima Kuhakarn; Jatuporn Meesin (Asian Journal of Organic Chemistry, 2025)
Abstract This work reports a new route for the synthesis of 3‐(9 H ‐fluoren‐9‐ylidene)indolin‐2‐one derivatives via the reaction of 3‐chlorooxindoles and O ‐ethyl S ‐(9 H ‐fluoren‐9‐yl) carbonodithioates mediated by 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU). The reactions readily proceeded at room temperature, enable a collection of 3‐alkenyl oxindoles to be prepared within a short reaction time (15 minutes). The 3‐alkenyl oxindoles can be easily converted to 3‐fluorenyl oxindoles by NaBH 4 reduction.
Keywords: Fluorine in Organic Chemistry; Organic Chemistry Cycloaddition Reactions; Chemical Synthesis and Reactions